2003
DOI: 10.1016/s0002-9440(10)64282-4
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Wnt/β-Catenin Pathway Activation in Idiopathic Pulmonary Fibrosis

Abstract: To investigate the molecular events that may underpin dysfunctional repair processes that characterize idiopathic pulmonary fibrosis/usual interstitial pneumonia (IPF/UIP), we analyzed the expression patterns of beta-catenin on 20 IPF/UIP lung samples, together with two downstream target genes of Wnt signaling, cyclin-D1, and matrilysin. In 18 of 20 cases of IPF/UIP investigated on serial sections, nuclear beta-catenin immunoreactivity and abnormal levels of cyclin-D1 and matrilysin were demonstrated in prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
536
5
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(562 citation statements)
references
References 64 publications
18
536
5
3
Order By: Relevance
“…Aberrant activation of the Wnt/␤-catenin signaling pathway has been proposed as a potential molecular event leading to dysregulated repair in the fibrotic lung (41). Our findings indicate that several components of the Wnt signaling pathway are differentially expressed in the lungs of patients with IIP; for example, SFRP2 is almost fourfold upregulated in the diseased tissue.…”
Section: Discussionmentioning
confidence: 64%
“…Aberrant activation of the Wnt/␤-catenin signaling pathway has been proposed as a potential molecular event leading to dysregulated repair in the fibrotic lung (41). Our findings indicate that several components of the Wnt signaling pathway are differentially expressed in the lungs of patients with IIP; for example, SFRP2 is almost fourfold upregulated in the diseased tissue.…”
Section: Discussionmentioning
confidence: 64%
“…Recent evidence has identified ␤-catenin, a powerful regulator of cell proliferation, as a key effector in fibrosis of both pulmonary and extrapulmonary organs. 41 Chilosi et al 18 reported evidence of aberrant Wnt/ ␤-catenin activation in fibroproliferative bronchiolar lesions and also nuclear ␤-catenin accumulation in the fibroblastic foci in lung samples from patients with IPF. More recently, Konigshoff et al 30 reported that WISP1, a target gene of the Wnt/␤-catenin pathway, is a key regulator of pulmonary fibrosis through its ability to induce collagen matrix deposition by fibroblasts and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cyclin D1 immunohistochemistry and ␤-catenin immunofluorescence staining (both from Cell Signaling Technology, Danvers, MA) were performed on paraffin-embedded lung tissue. 18,19 Briefly, lung tissue sections were deparaffinized and rehydrated. Antigen retrieval was performed by boiling slides in sodium citrate buffer (pH 6.0) for 10 minutes.…”
Section: Lung Histology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The sections from tissue blocks of MiTF/TFE family translocation carcinomas and control cases were immunolabeled with cathepsin-K using two different antibodies (clone CK4, Novocastra, Newcastle, UK and clone 3F9, Abcam, Cambridge, UK) and MiTF (clone D5, Neomarkers/LabVision, Fremont, CA, USA), using previously described methods. 18 Heat-induced antigen retrieval was performed using a microwave oven and 0.01 mol/l of citrate buffer, pH 8.0, for 30 min. All samples were processed using …”
Section: Immunohistochemical Analysismentioning
confidence: 99%